Lokaal 01 Antwerpen 2010. - Vergaert, Frederik; Vanbesien, Robin; Van Beek, Jozefien; Vervoort, Stefaan; Vos, Rieke; Devriendt, Indra; Lokaal 01, Antwerpen (Antwerpen : Lokaal 01, 2011)
Echigo, Masashi ; Detige, Ronald ; Mackay, Fiona ; Van Ingelgem, Herman ; De Beuckeleer, Nathan ; De Leener, Eva ; Crabeels, Cel ; Vervaet, Filip ; Vogelaers, Martijn ; Vanrooy, Esther ; Demeulenaere, Hans ; et al.
Overzicht tentoonstellingen in Lokaal 01 Antwerpen in 2010.
kunstcatalogus